Axial behavior of slender RC square columns strengthened with circular steel tube and sandwiched concrete jackets. (15th January 2019) - Li, Weijie; Liang, Hongjun; Lu, Yiyan; Xue, Jifeng; Liu, Zhenzhen
Highlights: Eight slender RC columns were strengthened with steel tube and sandwiched concrete jackets. The experimental results showed that the mechanical properties of the RC columns were enhanced. An accurate FE model was developed to simulate the response of the retrofitted columns. A modified load-bearing capacity prediction model was proposed. Abstract: Steel tube and sandwiched concrete jacketing has been proved to be effective in improving the load-bearing capacity and ductility of deficient reinforced concrete (RC) stub columns. However, the effectiveness of this technique for slender RC columns remains to be validated due to instability problems. In this study, nine slender specimens, including one reference column and eight retrofitted columns, were tested under axial compression. The experimental results showed that the load-bearing capacity, stiffness and ductility of the slender RC square columns were significantly enhanced. The load enhancement was not only attributed to section enlargement, but also due to the confinement provided by the steel tube. Based on the experimental results, a finite element (FE) model was developed to simulate the structural response of the retrofitted slender columns under axial load. The FE results demonstrated that the sandwiched concrete shared a higher load than the steel tube for the cross-section of this paper, justifying the use of "steel tube and sandwiched concrete jacketing". Moreover, the confinement effects on the load-bearing capacity of the RC part and the sandwiched concrete part were quantitatively analyzed. A modified formula was subsequently proposed to predict the load-bearing capacity of the retrofitted columns, the results of which agreed well with the experimental and FE results.